Strain Induced by Bio-High-Performance Polymers and Cobalt-Chromium Digitally Constructed Telescopic Partial Dentures after 1 Year Simulation of Function - Muwafi, Mohammed; Sabet, Marwa; Thabet, Yasmine (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Numerous attempts were made to reduce the adverse effects of the distal extension removable partial dentures (RPDs) and enhance their prognosis. High-performance polymers (HPP) were utilized in the construction of RPDs to maintain the health of the supporting structures. AIM: Thus, this study was prompted to compare the strains induced by Bio HPP and Cobalt- Chromium (Co Cr) Computer Assisted Design and Computer Assisted Manufacturing telescopic RPDs after 1 year of function. MATERIALS AND METHODS: A maxillary Kennedy class I was used in this study. Twelve telescopic RPDs were fabricated from two different materials. In Group A, six telescopic RPDs were milled from Co-Cr and in Group B, six telescopic retained RPDs were milled from Bio-HPP. Each partial denture was seated on the cast and introduced into the chewing simulator. The strain values were recorded using four strain gauges connected to a four-channel strain indicator. Statistical analysis of the resultant data was done using one-way ANOVA, followed by Tukey’s HSD for comparison within the same group. Student t-test was used for comparison between the different groups. The significance level was set at p ≤ 0.05. RESULTS: During unilateral loading, the results showed higher strains in Group A at the abutments (473.33 μm/m ± 10.8, 193.39 μm/m ± 10.8) and at the distal aspect of the ridge (470.83 μm/m ± 13.93, 185 μm/m ± 20.83) than Group B. Independent t-test showed statistically significant difference between strains at the abutments of both groups (t = 70.4, p ≤ 0.0001), (t = 36.84, p ≤ 0.0001). Furthermore, there was a statistically significant difference between strains at the saddles of both groups (t = 51.62, p ≤ 0.0001), (t = 34.72, p ≤ 0.0001) respectively (DOF = 10). CONCLUSIONS: In telescopic RPDs, Co Cr induces higher strain values on the abutments and the distal aspect of the ridge than Bio-HPP during bilateral and unilateral loading. During unilateral loading, Bio-HPP telescopic RPDs direct high strain values on the distal aspect of the ridge of the loaded side. CLINICAL IMPLICATIONS: The materials that induce less stresses on the supporting structures of telescopic partial dentures on the long-term can be used to maintain the health of periodontally affected abutments.